Perspective Transformation through Small Group Discipleship among Undergraduate University Students in Nairobi, Kenya - Mwangi, Mary Wanjiru (Christian education journal, 2018)
This study explored ways in which participating in small group discipleship fosters perspective transformation among undergraduate university students. Sixteen college students, who had participated in small group discipleship for two or more years, were interviewed. Also, two focus group interviews, constituted of small discipleship group leaders, were conducted for triangulation. The findings revealed perspective transformation was fostered through connectedness to God, individual engagements, transformational pedagogy, transformative relationships, and mentoring. The study highlighted the need for teaching foundational knowledge about the Christian faith, equipping learners to: practice spiritual disciplines, do ministry, and competently carry out successful Christian lives, relationships, and mentoring.